2017
DOI: 10.3390/ma10111238
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Ceramic Nanofiber Mats Today: Synthesis, Properties, and Applications

Abstract: Ceramic nanofibers (NFs) have recently been developed for advanced applications due to their unique properties. In this article, we review developments in electrospun ceramic NFs with regard to their fabrication process, properties, and applications. We find that surface activity of electrospun ceramic NFs is improved by post pyrolysis, hydrothermal, and carbothermal processes. Also, when combined with another surface modification methods, electrospun ceramic NFs result in the advancement of properties and wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(70 citation statements)
references
References 181 publications
(222 reference statements)
0
62
0
Order By: Relevance
“…Electrospinning is a powerful and straightforward technology that utilizes high electrostatic force to produce continuous polymeric micro/nano fibers [6,7]. It has been well demonstrated that the coexisting strong electric fields and stretching force in the process of electrospinning can align the dipole moment in the PVDF fibers' crystal, endowing the unique piezoelectricity no matter how traditional far-field electrospinning or near-field electrospinning are utilized [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a powerful and straightforward technology that utilizes high electrostatic force to produce continuous polymeric micro/nano fibers [6,7]. It has been well demonstrated that the coexisting strong electric fields and stretching force in the process of electrospinning can align the dipole moment in the PVDF fibers' crystal, endowing the unique piezoelectricity no matter how traditional far-field electrospinning or near-field electrospinning are utilized [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Several routes are available for the preparation of nanostructured ceramic NPs and NFs, including sol-gel, crystallization from molten salts, combustion synthesis, and melt spinning [24][25][26]. However, the electrospinning method presents a simple and cost-efficient process that yields continuous fibers with average diameters of nano to micrometers [27,28]. In fact, electrospinning has recently facilitated the synthesis of nanocomposite particles and nanostructured thin films [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…There are two approaches toward developing ceramic NFs via the electrospinning procedure: ceramic reagents are either blended as ceramic NPs or dissolved into a polymer solution as ceramic precursors. It should be added that post-heat treatment may regulate the final product as amorphous to highly crystalized ceramic NFs [28].…”
Section: Introductionmentioning
confidence: 99%
“…In this method, first, an electrospinnable solution is prepared with the help of some processes such as sol-gel or simple mixing of a polymer with precursor or metal salts. Then, the electrospinning of solution containing mineral precursor to fabricate nanofibers is followed by calcination at high temperature [6,7]. The ceramic nanofibers produced by this method show unparalleled characteristics and properties, such as one-dimensional morphology, high length, porosity, high magneticity, and a high surface area [8].…”
Section: Introductionmentioning
confidence: 99%